Behavioral inattention and human capital accumulation - Barrón Ayllón, Manuel Fernando (2019)
I use data from a standardized test applied to second and eighth graders in rural Peru to show that inability to correctly interpret test scores can affect schooling outcomes persistently. Marginally classifying as “remedial” in second grade math reduces rural males’ eighth grade scores by 0.18 standard deviations, compared to students that obtained marginally higher scores and were classified as “in transition” in second grade. Since students, parents, and teachers receive both the score and the label attached to it, this is evidence of behavioral inattention. Besides being the first study to provide evidence of behavioral inattention in human capital accumulation in a developing country setting, this study provides novel evidence on the mechanisms at play. I show that results owe to classroom environment and household resource reallocation. Rural males who barely classified as remedial in second grade are more likely to work, have fewer books available at home, and perceive a more negative classroom environment by eighth grade than those who obtained marginally higher scores. These findings have important implications for educational policy, in particular to the communication of standardized test scores.